Effects of Warm Temperatures on Ovarian Development of Walking Catﬁsh Clarias macrocephalus (Günther, 1864) During Post-Spawning Season - Poompoung, Pornpun; Poompuang, Supawadee; Kamonrat, Wongpathom (Agriculture and Natural Resources, 2012)
This study aimed to determine the possibility of using temperature manipulation to stimulate ovarian activities of Clarias macrocephalus during the post-spawning season. The ovarian development and monthly change in the gonado-somatic index (GSI) of females held under pond conditions was monitored over a 1 yr period from April 2008 to March 2009. In October, 13 mth-old female ﬁ sh (weight ± SD= 108 ± 12.7 g) were randomly collected from an earthen pond and exposed to different temperatures at 25, 30 and 35 °C under hatchery conditions for 6 wk. The results indicated that the change in the GSI appeared to be correlated with the amount of rainfall, but not to the variation in seasonal temperature. A signiﬁ cant (P < 0.05) variation of mean GSI values was observed among months with the highest value ± SE (13.91 ± 3.63%) in July. Histological examination of ovaries revealed that in females held under 25, 30 and 35 °C, the number of vitellogenic oocytes progressively increased from 0.5–4.7% at week 2 to 4.6–19.7% at week 6, whereas in females held in the earthen pond, ovaries contained only immature oocytes. Exposure to warm temperatures resulted in signiﬁ cant elevations of plasma cortisol but not glucose concentrations. Although fully matured females could not be obtained, the present study suggested that temperature manipulation was probably the practical way to increase the number of maturing females during the off reproductive season for walking catﬁsh.